PERAN MODAL SOSIAL DALAM PENINGKATAN EFEKTIFITAS KERJA KARYAWAN INDUSTRI RUMAHAN TEMPE DAN TAHU DI KECAMATAN SINJAI UTARA - Hikmah, Aulia Nurul; Asma, Annisa Fahira; Salmawati, Salmawati; Fatimah, St; Zalsabila, Annisa; Ardiansya, Ardiansya (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2025)
This study examines the role of social capital in improving the work effectiveness of tempeh and tofu home industry employees in North Sinjai District. The research used a qualitative approach with data collection techniques through interviews, observations, and questionnaire tools involving 30 business actors and 30 employees. The results showed that social capital, including social networks, trust, and cooperation norms, improved work effectiveness. The results revealed that social capital, including social networks (kinship), trust, and the value of cooperation, is essential in encouraging work productivity and efficiency. 25 tofu and tempeh home industries (83%) apply family-based social networks to facilitate labor recruitment and raw material distribution, while trust (73%) between business owners and employees can reduce formal supervision. In addition, the tradition of gotong royong (70%) is applied to accelerate work completion and strengthen solidarity among workers.